English Language in the British education system in Malaya : implementation and implications - Khairi Ariffin,; Azlizan Mat Enh, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study is about the development of English in Education in Malaya before independence. Christian missionaries pioneered education in English at an early stage in Malaya. The position of English in the education system in Malaya in the colonial era has gained a better status compared to the position of Malay and other vernacular languages. This study uses a qualitative method with an emphasis on document and manuscript analysis. This study was conducted at the National Archives of Malaysia and involved the study and analysis of official documents such as the Annual Report, the Education Report, the Colonial office file and official records of the British colonial government. The study's findings have shown that the development of English education started with the opening of English schools by Christian missionaries and the English schools established by the colonial government. There were various reactions to English education from the community, with an encouraging response among the Malayan people. The development of English education created opportunities for people to pursue higher education abroad and within the country. In conclusion, English education has succeeded in producing many students who have successfully placed themselves in the service of the British government. The implementation of English education has been able to help increase the knowledge of current and future generations about the history and emergence of English education in Malaysia.